Perception of mental health professionals on the use of exercise to promote mental health and well-being (2013)
The aim of this study is to assess the psychiatric health workers' perception on the use of exercise to promote mental health and well being. One hundred and thirty eight (138) randomly sampled psychiatric health care givers in three (3) psychiatric hospitals were selected for the study. Questionnaires was used to collect data for analysis. There was high level of willingness to include exercise in the management of mental health. Virtually all the respondents agreed that exercise is a viable adjunct to traditional therapies. However, the use of exercise in promotion of mental health is not well defined during training of the respondents. Mandatory course on exercise and mental health during training for initial certification to work as psychiatric health worker was therefore recommended.